PENALARAN MORAL ANAK DITINJAU DARI GAYA PENGASUHAN DAN JENIS KELAMIN - Hayani, Nur (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2018)
The objectives of this research is to know the difference of moral reasoning between boys and girls perceived from authoritarian, authoritative and permissive parents. The subjects of this research were 81 students at primary school of Al Falah Sei Mencirim Kutalimbaru Sumatera Utara. The data of the study was collected by using two scales, they are Moral Reasoning scale and parenting style scale. Analysis of Variance (ANOVA) was applied to analyze the data, which resulted that parenting styles and gender interact each other in affecting moral reasoning (F : 5,580; p = 0.006 < 0.05), and it means that there is a difference of moral reasoning among boys and girls perceived from authoritarian, authoritative and permissive parenting styles. Based on the finding above, it is suggested that educators should develop suitable teaching strategy which may enhance positive developmental aspects by avoiding sex stereotypes; encouraging to be independent and take a risk; and guiding in problem solving. It is suggested too that parents should avoid different parenting between boys and girls and help them to make moral decision properly so the can avoid social adapting problems.